What is a Transformative Approach to Care, and Why Do We Need It? - Esquivel, Valeria Renata (2014)
The meanings of care are contested – the approaches to care in the development and feminist literature have varied greatly. At the same time, care is a common word, loaded with moral meanings concerning notions of duty and love, and care is commonly associated with women. These associations are not innocent; they have concrete effects in shaping different policy agendas and institutional responses to care and care work. While the feminist meanings of care stem from feminist philosophy, feminist economics, and feminist social policy research, these meanings compete with the more conservative and traditional meaning of care in the development discourse. This article provides a conceptual introduction to care, and aims to show how the different understandings of it affect the ways policymakers approach the issue. Depending on the way care is framed, policies and practices can be designed and implemented in transformative ways, in the sense of supporting carers – predominantly women – and lightening their care burdens, while challenging the notion that this work is intrinsically ‘female’ and of lesser importance than work seen as ‘productive’. The article invites development practitioners to reflect on their own views about care, and to identify what can be done to recognise, reduce, and redistribute care at multiple levels.